KADAR PROTEIN DAN KUALITAS TEPUNG JAMUR TIRAM PUTIH (Pleurotus ostreatus) DENGAN PERENDAMAN KONSENTRASI CaCO3 DAN SUHU YANG BERBEDA - Nugroho, Agung, Dr. Siti Chalimah, M.Pd (2015)
White oyster mushroom is one type of healthy vegetables that are already widely known and consumed by the public. The protein content of white oyster mushroom (JTP) is quite high and can be processed into flour. Soaking using CaCO3 aims to strengthen and prevent browning. The research objective of this modified starch manufacture JTP and determine levels of soluble protein, moisture content, and test the organoleptic properties of the JTP. The method used in this study is a research method experiment with completely randomized design (CRD) using two factors. The first factor is the temperature of the oven 300C, 400C, 500C. The second factor is the concentration of CaCO3 as much as 3%, 5% and 7% with three replications. Parameters measured include protein content, moisture content and the organoleptic properties of the protein content of the data analysis munggunakan friedman test, while the water content and organoleptic test using a two way ANOVA. The results showed the highest protein levels at treatment temperature of 500C and without CaCO3 concentration is 2.63%. The highest water levels at treatment temperature of 500C and without CaCO3 concentration is 93.10%. Best color at a temperature of 400C immersion treatment of 7% and a temperature of 500C immersion 5% white. Texture best at a temperature of 400C immersion treatment of 5% and 7% 400C immersion. Best organoleptic properties at a temperature of 500C and soaking treatment CaCO3 concentration of 5% and 7%.